Environmental and Clinical Strains of Vibrio cholerae Non-O1, Non-O139 From Germany Possess Similar Virulence Gene Profiles - Schwartz, Keike; Hammerl, Jens Andre; Göllner, Cornelia; Strauch, Eckhard (Frontiers in Microbiology, 2019)
Vibrio cholerae is a natural inhabitant of aquatic ecosystems globally. Strains of the serogroups O1 and O139 cause the epidemic diarrheal disease cholera. In Northern European waters, V. cholerae bacteria belonging to other serogroups (designated non-O1, non-O139) are present, of which some strains have been associated with gastrointestinal infections or extraintestinal infections, like wound infections or otitis. For this study, environmental strains from the German coastal waters of the North Sea and Baltic Sea were selected (100 strains) and compared to clinical strains (ten isolates) that were from patients who contracted the infections in the same geographical region. The strains were characterized by MLST and examined by PCR for the presence of virulence genes encoding the cholera toxin, the toxin coregulated pilus, and other virulence-associated accessory factors. The latter group comprised hemolysins, RTX toxins, cholix toxin, pandemic islands, and type III secretion system (TTSS). Phenotypic assays for hemolytic activity against human and sheep erythrocytes were also performed. The results of the MLST analysis revealed a considerable heterogeneity of sequence types (in total 74 STs). The presence of virulence genes was also variable and 30 profiles were obtained by PCR. One profile was found in 38 environmental strains and six clinical strains. Whole genome sequencing (WGS) was performed on fifteen environmental and seven clinical strains that were ST locus variants in one, two or three alleles. Comparison of WGS results revealed that a set of virulence genes found in some clinical strains is also present in most environmental strains irrespective of the ST. In few strains, more virulence factors are acquired through horizontal gene transfer (i.e. TTSS, MSHA pilus, genomic islands). A distinction between clinical and environmental strains based on virulence gene profiles is not possible for our strains. Probably, many virulence traits of V. cholerae evolved in response to biotic and abiotic pressure and serve adaptation purposes in the natural aquatic environment, but provide a prerequisite for infection of susceptible human hosts. These findings indicate the need for surveillance of Vibrio spp. in Germany, as due to global warming abundance of Vibrio will rise and infections are predicted to increase.